2018
DOI: 10.3389/fendo.2018.00536
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Modulates MicroRNAs 29b-3p, 29c-3p, 199a-5p and 532-3p Expression in Muscle: Possible Role in GLUT4 and HK2 Repression

Abstract: The reduced expression of solute carrier family 2, facilitated glucose transporter member 4 (GLUT4) and hexokinase-2 (HK2) in skeletal muscle participates in insulin resistance of diabetes mellitus (DM). MicroRNAs (miRNAs) have emerged as important modulators of mRNA/protein expression, but their role in DM is unclear. We investigated miRNAs hypothetically involved in GLUT4/HK2 expression in soleus muscle of type 1 diabetes-like rats. In silico analysis revealed 651 miRNAs predicted to regulate solute carrier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 66 publications
0
52
0
Order By: Relevance
“…Among the miRNAs also associated with serum C-peptide concentration, we identified plasmatic miR-29c-3p, which was univocally up-regulated in children who manifest DKA at T1D diagnosis (Figure 4). Several studies in mice and rats have associated miR-29c-3p dysregulation with impaired glucose transporter expression and glycemic control in skeletal muscle, exacerbated vascular remodeling, and hepatic negative regulation of insulin signaling in diabetes [59][60][61][62]. Less information is available on the involvement of miR-29c-3p in human diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Among the miRNAs also associated with serum C-peptide concentration, we identified plasmatic miR-29c-3p, which was univocally up-regulated in children who manifest DKA at T1D diagnosis (Figure 4). Several studies in mice and rats have associated miR-29c-3p dysregulation with impaired glucose transporter expression and glycemic control in skeletal muscle, exacerbated vascular remodeling, and hepatic negative regulation of insulin signaling in diabetes [59][60][61][62]. Less information is available on the involvement of miR-29c-3p in human diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have revealed the decrease of SIRT1 in diabetes patients (Balestrieri et al, 2013) and the increase of miR-29b-3p in diabetes (Esteves et al, 2018). Furthermore, Su et al (2019) have proved the direct regulation of miR-29b-3p to SIRT1 in insulin resistance.…”
Section: Introductionmentioning
confidence: 95%
“…It also regulates cardiomyocyte apoptosis by targeting JunB (JunB proto-oncogene) [37]. In diabetic individuals, miR-199a-5p may be involved in skeletal muscle insulin resistance by inhibiting glucose transporter 4 (GLUT4) and hexokinase 2 (HK2) [38]. MiR-199a-5p also participates in lipid metabolism,in Italian Large White pigs, miR-199a-5p showed a higher expressional level in the backfat of the lean groups than that in the fat group [39].…”
Section: Discussionmentioning
confidence: 99%